Improving Asthma Care Documentation with a Digital Tool–Experience in a Pediatric Institution - de Groot, Stormie; Lawrence, Joanna; Liddle, James; Campbell, Janice; Cheng, Daryl R. (Applied Clinical Informatics, 2022)
Background Asthma affects approximately 10% of Australian children. Electronic medical record (EMR) systems and clinical decision support initiatives have been shown to improve the delivery of asthma care. Our institution implemented an EMR-based asthma “hub,” which collates asthma-related information to a central location within a patient's record, provides a template to collect relevant clinical information, allows clinicians to evaluate a patient's history and presentation in a systematic manner and prompts relevant actions.Objective The aim of the study is to measure year-on-year improvement in asthma-related documentation and provide a key gold-standard aspects of asthma management after the introduction of an EMR asthma “hub” tool in the outpatient setting.Methods The asthma “hub” was introduced in November 2020. A chart review was conducted of all patients who attended the Complex Asthma Clinic between January-April 2020 and January-April 2021. The provision and presence of documentation of core aspects of asthma care were described in percentages and comparisons of pre- and post-introduction of the asthma “hub” were assessed.Results There was a significant increase in the documentation of asthma triggers, including smoking/smoker exposure, (47.5–92.6%, p <0.001), current asthma action plans (70.4–86.3%, p = 0.02), and severity scores (46.3–81%, p <0.001) post the introduction of the asthma “hub.” There was no significant difference in documentation of reliever (as required) or regular preventer medications.Conclusion An evidence-based EMR intervention improved the documentation and provision of aspects of asthma care in an outpatient clinic setting at a tertiary pediatric hospital, suggesting replication in the inpatient and emergency settings would be worthwhile. Further research is required to understand the tool's impact on clinical outcomes and on clinical efficiency and workflow.
Keywords: asthma; pediatric hospital; informatics; electronic medical record